Unveiling the Complexity of Earth's Dynamic Ecosystems: Harnessing the Power of Remote Sensing for Environmental Analysis - Ahmad Basir Ahmadi; Mustafa Mohammadi; Zabihullah Nadry; Abdulrazaq Nazari; Sohaila Arghawan (Indonesian Journal of Earth Sciences, 2023)
Remote sensing has become an indispensable tool within geographic studies, fundamentally reshaping our understanding of the Earth's dynamic processes and surface. This comprehensive review article explores the diverse and multifaceted applications of remote sensing across various geographic disciplines. It commences by providing a comprehensive overview of the evolution and underpinning technology of remote sensing. Subsequently, the paper proceeds to delve into the methodological intricacies commonly employed in remote sensing studies, followed by an in-depth and systematic review of relevant literature. This meticulous review elucidates key findings and pioneering advancements and highlights the prevalent challenges experienced in diverse geographic domains. The empirical outcomes of this review underscore the profound importance of remote sensing as an invaluable tool for mapping vegetation areas. Furthermore, the findings gleaned from this extensive inquiry underscore the considerable contribution of remote sensing in enhancing our understanding of urban studies. This manifests through its capacity to furnish detailed insights into urban morphology, land use patterns, and the dynamic urban growth processes. The research outcomes vividly illustrate that water resources management derives substantial benefits from the intrinsic capabilities of remote sensing. Its capacity to capture and provide crucial water quality parameters and aquatic ecosystems empowers water resource professionals with a wealth of indispensable data. Moreover, the findings of this comprehensive review concretely establish the irreplaceable role of remote sensing in assessing natural hazards, spanning from landslides to volcanic activity. The empirical evidence presented is a testament to the importance of integrating remote sensing data with Geographic Information Systems (GIS). This interaction has revolutionized spatial data analysis and visualization, underscoring the transformative potential of combining these two technological domains.